Risk management and firm performance: the role of dynamic capability and risk management culture - AMISSAH MICHAEL KOJO (KNUST, 2024)
Thesis submitted to the department of supply chain and information s systems, knust school of business, in partial fulfillment of the requirement for the award of the degree of msc. Business administration (procurement and supply chain management)